Effect of Acetic Acid and Lactic Acid at Low pH in Growth and Azole Resistance of Candida albicans and Candida glabrata - Lourenço, Andreia; Pedro, Nuno Alexandre; Salazar, Sara Barbosa; Mira, Nuno Pereira (Frontiers in Microbiology, 2019)
Successful colonization of the acidic vaginal niche by C. glabrata and C. albicans depends on their ability to cope with the presence of lactic and acetic acids produced by commensal microbiota. As such, the inhibitory effect of these acids at a low pH in growth of C. glabrata and C. albicans was investigated. The effect of the presence of these organic acids in tolerance of the two Candida species to azoles used in treatment of vaginal infections was also investigated including eventual synergistic effects. Under the different experimental conditions tested lactic acid exerted no significant inhibitory effect against C. albicans or C. glabrata, contrasting with the generalized impression that the production of this acid is on the basis of the protective effect exerted by vaginal lactobacilii. Differently, C. glabrata and C. albicans exhibited susceptibility to acetic acid, more prominent at lower pHs and stronger for the latter species. Synergism between acetic acid and azoles was observed both for C. albicans and C. glabrata, while lactic acid-azole synergism was only efficient against C. albicans. Altogether our results indicate that tolerance to acetic acid at a low pH should play a more relevant role than tolerance to lactic acid in determining competitiveness in the vaginal tract of C. albicans and C. glabrata including under azole stress. Treatment of vaginal candidiasis with azoles may depend on the level of acetic and lactic acids present and improvements could be achieved synergizing the azole with these acids.